Depicting history in the "novel chronicle" Šikmý kostel by Karin Lednická - Mikešová, Iveta (Bohemica Olomucensia, 2023)
The article considers the role of historical fiction in Czech literature since the year 2000 and analyzes the depiction of history within the genre of family saga and novel chronicle based on the example of the first two volumes of Karin Lednická's intended trilogy Šikmý kostel (2020, 2021).
Keywords: Czech literature; historical fiction; novel chronicle; family saga; Karin Lednická